DIGITAL TRANSFORMATION AND INTERNATIONAL COMPETITION: ANALYSIS OF THE IMPACT OF DIGITAL TECHNOLOGIES ON COMPETITIVENESS AND DEVELOPMENT OF INTERNATIONAL BUSINESS (American Journal of Business Management, Economics and Banking, 2024)
The rapid development of digital technologies has transformed the global business landscape, creating new opportunities for international competition and growth. This article analyzes how digital transformation influences the competitiveness of businesses in the global marketplace. The study explores the role of key digital technologies such as artificial intelligence (AI), big data, cloud computing, and blockchain in enhancing business processes, improving efficiency, and fostering innovation. By examining case studies of companies that have successfully integrated digital technologies, this article also highlights the challenges faced by businesses in adopting digital solutions and the broader implications for international competition. The findings suggest that companies that embrace digital transformation are better positioned to compete internationally, while those that fail to adapt risk falling behind in the global economy.